Thermal desorption effects on fragment ion production from multi-photon ionized uridine and selected analogues - Bocková, Jana (2021)
FuEP/E039618/1 EP/J002577/1 EP/L002191/1 MERG-CT-2007-207292 no. 692335 VEGA 1/0489/21 APVV-19-0386 PD/00193/2012 UID/FIS/00068/2020 UID/Multi/04378/2020